Demographic Profiles and the Percieved-Actual Responses of the Grade 7 History Teachers on the Implementation of the K-12 Curriclum in the Province of Sulu - Mohammad, Abdulla I. (Open Access Indonesia Journal of Social Sciences, 2021)
The primary aim of this paper was to determine the demographic profiles and the percieved-actual responses of the grade 7 history teachers on the implementation of the K-12 curriclum in the Province of Sulu. The descriptive research design was used in the study. The study was conducted in Sulu both private and public schools. The study participants were composed of Grade 7 History teachers in public and private High Schools in some of the municipalities, province of Sulu for school year 2017-2018. The results concluded that The Grade 7 History teachers are not growing professionally in terms of their educational attainment both in perceived and actual implementation of the K-12 curriculum, they strongly agreed that the following problems exist: as Learning Resources, Teacher’s Competency, Method Approaches and Technique, Administrator’s Competency and Teaching, Supervisor’s Competency, Monitoring, Technical Assistance, Evaluation, and Assessment. It is recommended that Based on the findings of the study on the issues and challenges confronting Grade 7 History teachers in the implementation of K-12 curriculum in the Province of Sulu, the following recommendations are: Grade 7 History teachers must improve their education attainment;History teachers spontaneously read more about techniques, strategies about History on the implementation of K-12 curriculum;History teachers must earn at least Master’s degree in line with his or her major; The DepEd must improve the implementation of the K-12 History curriculum in areas of Learning Resources, Teacher’s Competency: Method Approaches and Technique, Administrator’s Competency and Teaching, Supervisor’s Competency, Monitoring, Technical Assistance, Evaluation, and Assessment; The DepEd must sponsor more seminars for the History Teachers to participate in the actual implementation of the K-12 History Curriculum; There must be similar study conducted to assist the findings of this study; and Administration must fully support the program; that is and for the progress of the teachers.